The The Effect of Bridging Exercise to Improve Balance In Post Stroke Patients at Kartini Hospital Jepara - Mutiara Intani (Institute of Computer Science (IOCS), 2022)
Stroke is a multi-factorial disease with various types of causes accompanied by major clinical manifestations and the main cause of disability and death in developing countries. Impaired standing balance in stroke patients is a very influential disorder and greatly disrupts the activities of post-stroke patients. With these problems, post-stroke patients have difficulty in carrying out independent activities so that they need a good balance. The body's ability to maintain balance or maintain a body of center is regulated by the higher central nervous system through the reception of non-impulse regulation. One of the interventions given is bridging exercise. This exercise was measured using the Berg Balance Scale (BBS) outcome measurement. The purpose of this study was to determine the effect of bridging exercise to improve the balance of post-stroke patients at the Kartini Jepara Hospital. The research method uses an experimental study with a single case report approach. The study was conducted at a hospital in Jepara City on a post-stroke SNH patient named Mr. S, 65 years old, Muslim and a carpenter. Based on the results of the pre-test and post-test scores, it can be concluded that Bridging Exercise has an effect on the balance of post-stroke patients.